2016
DOI: 10.18203/2320-1770.ijrcog20164648
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study of fetomaternal outcome in pregnancy with polyhydramnios

Abstract: Background: Amniotic fluid not only provides protection to the fetus from traumatic forces, cord compression, and microbial pathogens, but also plays an integral role in the normal development of the fetal musculoskeletal, pulmonary, and gastrointestinal systems. Polyhydramnios, defined as an excessive amount of amniotic fluid, complicates approximately 0.4-3.3% of all pregnancies. Fetal conditions that are associated with polyhydramnios include major congenital anomalies and both the immunologic and non-immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 8 publications
(9 reference statements)
1
10
3
Order By: Relevance
“…14 Anencephaly was the topmost anomaly in a study done at India. 9 Cleft lip and palate was responsible for 4.6% of congenital anomalies in our study whereas 5% of them was present in an International study. 9 Polyhydramnios was seen most commonly in women in age range 31 -40 years, followed by 21 -30 years age group according to our research.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…14 Anencephaly was the topmost anomaly in a study done at India. 9 Cleft lip and palate was responsible for 4.6% of congenital anomalies in our study whereas 5% of them was present in an International study. 9 Polyhydramnios was seen most commonly in women in age range 31 -40 years, followed by 21 -30 years age group according to our research.…”
Section: Discussioncontrasting
confidence: 46%
“…13 Similarly Akram H et al noticed 51% cases of 31 -40 years age 15 .49% of our cases were multigravidas, whereas 59.9% were multigraviads in another study. 9 Likewise 57% were multigravidas in study by Chaurasia S et al 14…”
Section: Discussionmentioning
confidence: 95%
“…In our study we found mild hydramnios in 95% patients and only 5% had moderate to severe hydramnios. Desmedt et al (8) found in their 10 year study in 537 patients with polyhydramnios that 5.9% patients had preexisting diabetes and 3% had gestational diabetes.in another study by Rajgire AA et al (9) about 58.1% cases of polyhydramnios had associated maternal condition of which maximum cases had preeclampsia (16.6%) and anaemia (16.6%) followed by gestational diabetes mellitus (8.3%) followed by Rh isoimmunization (6.6%). Gita Guin et al (10) found in their study that diabetes mellitus was found in 20% of cases,PIH in 17.7%,twin pregnancy in 6.6% and Rh incompatibility in 4.4% .In our study there were associated factors like anemia in 27%, diabetes mellitus in 8%,multiple pregnancy in 6% and Rh negative in 6%of cases.…”
Section: Jmscr Vol||05||issue||07||page 25661-25666||july 2017mentioning
confidence: 95%
“…We found an incidence of 27% anemia, 22% malpresentations, 16% preterm labour, 15% pregnancy induced hypertension,10% intrauterine deaths, 6% PROM, 3% placenta previa, 1% abruption and 1% antepartum eclampsia in our patients. Rajgire AA et al (9) found in their study that about 31.4% of cases of polyhydramnios had complications like malpresentation (6.6%), preterm labour (5%), premature rupture of membrane (s5%), eclampsia( 5%), placenta previa (3.3%), and 3.3% patients developed postpartum haemorrhage. Least common were cord prolapse and placental abruption (1.6%) Gita Guin et al (10) found that the incidence of malpresentation was 13.3%, cord prolapse (11.1%) and PPH (4.4%) In their study, Sudha Chourasia et al (11) found that the common complications were preterm labour (16.3%) followed by PROM (3.7%) abruption placentae (2.9%) and PPH (2.9%) In our study 53% of patients were managed conservatively.…”
Section: Jmscr Vol||05||issue||07||page 25661-25666||july 2017mentioning
confidence: 96%
“…8 The perinatal outcome of polyhydramnios can be affected by certain complications like malpresentations, preterm labor, premature rupture of membranes, accidental haemmorhage, cord prolapse, uterine inertia, retained placenta, and postpartum haemmorhage. 9 Therapeutic amniocentesis is a method to deal with symptomatic polyhydramnios for the relief of respiratory distress. 10 Prostaglandin synthetase inhibitors like indomethacin and sulindac have been used in management of polyhydramnios as they reduce amniotic fluid volume by decreasing fetal urine output and enhancing resorption of lung fluid.…”
Section: Introductionmentioning
confidence: 99%